Cross-site analysis of perceived ecosystem service benefits in multifunctional landscapes. (May 2019) - Fagerholm, Nora; Torralba, Mario; Moreno, Gerardo; Girardello, Marco; Herzog, Felix; Aviron, Stephanie; Burgess, Paul; Crous-Duran, Josep; Ferreiro-Domínguez, Nuria; Graves, Anil; Hartel, Tibor; Măcicăsan, Vlad; et al.
Highlights: In ten countries 2, 301 residents mapped 28, 878 ecosystem service (ES) benefits. Outdoor recreation, aesthetic values and social interaction are key ES benefits. Settlement areas are ES benefit hotspots in multifunctional rural landscapes. Many ES are also related to forests, waters and mosaic landscapes. ES benefit perception links to relationship with and accessibility to a landscape. Abstract: Rural development policies in many Organization for Economic Co-operation and Development (OECD) member countries promote sustainable landscape management with the intention of providing multiple ecosystem services (ES). Yet, it remains unclear which ES benefits are perceived in different landscapes and by different people. We present an assessment of ES benefits perceived and mapped by residents (n = 2, 301) across 13 multifunctional (deep rural to peri-urban) landscapes in Europe. We identify the most intensively perceived ES benefits, their spatial patterns, and the respondent and landscape characteristics that determine ES benefit perception. We find outdoor recreation, aesthetic values and social interactions are the key ES benefits at local scales. Settlement areas are ES benefit hotspots but many benefits are also related to forests, waters and mosaic landscapes. We find some ES benefits (e.g. culture and heritage values) are spatially clustered, while many others (e.g. aesthetic values) are dispersed. ES benefit perception is linked to people's relationship with and accessibility to a landscape. Our study discusses how a local perspective can contribute to the development of contextualized and socially acceptable policies for sustainable ES management. We also address conceptual confusion in ES framework and present argumentation regarding the links from services to benefits, and from benefits to different types of values.